PKM : Inovasi Camilan Keripik Talas Sebagai Produk Unggulan Desa - Saeful Anwar; Raditya Danar Dana; Yudhistira Arie Wijaya; Rina Andriyanti; Novita Safitri (CV. Multi Kreasi Media, 2024)
Taro chips are a snack with significant potential as a village's flagship product. Despite their unique flavor and promising market potential, these products have not fully utilized innovations in flavor variety, packaging, and marketing. The lack of innovation in taro chips' flavor variety has made it difficult for the products to compete with similar snacks from other regions. Unattractive packaging reduces the product's appeal and potential sales in broader markets. Objective To enhance taro chips' product innovation by creating new flavor varieties that appeal to consumers and improve packaging quality to enhance visual appeal and product durability, thus enabling better market competitiveness. Method The implementation involved organizing workshops for entrepreneurs to introduce techniques for creating new flavor varieties for taro chips. This training involved culinary experts to provide practical guidance and create several new flavors that could be implemented. Marketing Support: Guidance on marketing strategies was provided to increase product visibility in the market, including using social media and e-commerce platforms. Results: The training resulted in the creation of five new flavor varieties for taro chips, which were well-received by consumers, such as sweet and spicy, cheese, balado, barbecue, and original flavors. Product packaging also saw significant improvements with the application of modern, more attractive, and functional packaging designs. Additionally, entrepreneurs showed increased sales and online marketing activities after the training.